2021
DOI: 10.3390/su132011431
|View full text |Cite
|
Sign up to set email alerts
|

Child-to-Parent Violence during Confinement Due to COVID-19: Relationship with Other Forms of Family Violence and Psychosocial Stressors in Spanish Youth

Abstract: This study analyzes child-to-parent violence during strict confinement due to COVID-19 as well as its association with other forms of family violence (parent-to-child violence and exposure to violence between parents) and with different psychosocial stressors: Academics/work, family coexistence, finances, COVID-19 and physical and psychological health. The study included 2245 young people (52.8% females) aged between 18 and 25 years (M = 21.52 years, SD = 2.07 years). The results show that more than half of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
4
12
1
Order By: Relevance
“…Perhaps, after a certain age, the degree of CPA perpetration remains more constant. The absence of a significant relation between CPA and academic failure also deviates from previous findings (Cano-Lozano et al, 2021b ; Cortina & Martín, 2020 ; Howard & Rottem, 2008 ; Rico et al, 2017 ). Possibly, the emerging adults ‘ transference from school into work rendered academic performance out of the equation (Arnett, 2000 ).…”
Section: Discussioncontrasting
confidence: 86%
“…Perhaps, after a certain age, the degree of CPA perpetration remains more constant. The absence of a significant relation between CPA and academic failure also deviates from previous findings (Cano-Lozano et al, 2021b ; Cortina & Martín, 2020 ; Howard & Rottem, 2008 ; Rico et al, 2017 ). Possibly, the emerging adults ‘ transference from school into work rendered academic performance out of the equation (Arnett, 2000 ).…”
Section: Discussioncontrasting
confidence: 86%
“…This exposure to violence at home can occur through the observation of violence (when children witness violence between their parents, for example) and through direct victimization (when children suffer violence from their parents). Consistent with this approach, recent studies have found that CPV is related to exposure to violence between parents (e.g., [ 7 , 11 , 13 , 21 ]) and to parent-to-child violence (e.g., [ 5 , 11 , 13 , 22 ]).…”
Section: Introductionmentioning
confidence: 80%
“…CPV has been related to various individual, family and social factors [ 6 , 12 ]. Given the context in which this type of violence takes place, the study of family variables takes on special importance, and, among them, exposure to family violence has received the most attention in the literature on this topic (e.g., [ 7 , 11 , 13 , 14 , 15 , 16 ]). Studies from the perspective of the intergenerational transmission of violence (e.g., [ 17 , 18 , 19 ]) propose that as a result of observational learning and imitation of adult models [ 20 ], children from violent homes are more likely to become violent since they internalize that aggression as an adequate way to cope with interpersonal conflicts.…”
Section: Introductionmentioning
confidence: 99%
“…This type of violent behavior also aims to dominate parents (Howard & Rottem, 2008). CPV is a form of family violence internationally recognized nowadays as a social problem, which has led to an increase of research in this topic in different countries (e.g., Beckmann, 2020;Cano-Lozano et al, 2021;Simmons et al, 2020).…”
Section: R E S U M E Nmentioning
confidence: 99%